1996
DOI: 10.1021/bi952955d
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Human DNA Polymerase β Complexed with DNA:  Implications for Catalytic Mechanism, Processivity, and Fidelity,

Abstract: Mammalian DNA polymerase beta (pol beta) is a small (39 kDa) DNA gap-filling enzyme that comprises an amino-terminal 8-kDa domain and a carboxy-terminal 31-kDa domain. In the work reported here, crystal structures of human pol beta complexed with blunt-ended segments of DNA show that, although the crystals belong to a different space group, the DNA is nevertheless bound in the pol beta binding channel in the same way as the DNA in previously reported structures of rat pol beta complexed with a template-primer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
282
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(291 citation statements)
references
References 78 publications
7
282
2
Order By: Relevance
“…6; strand 5 also includes the catalytic residue Asp-256 (not shown). The loop itself is disordered or solventexposed in crystal structures and is positioned at some distance from the active site (30,31). This makes it difficult to deduce what the role of this loop in substrate interactions could be.…”
Section: More Efficient Mispair Extension May Underlie the Mutatormentioning
confidence: 99%
“…6; strand 5 also includes the catalytic residue Asp-256 (not shown). The loop itself is disordered or solventexposed in crystal structures and is positioned at some distance from the active site (30,31). This makes it difficult to deduce what the role of this loop in substrate interactions could be.…”
Section: More Efficient Mispair Extension May Underlie the Mutatormentioning
confidence: 99%
“…Isoleucine 260 is located within a hydrophobic hinge region that appears to function in the movement of the fingers subdomain upon interaction of the polymerase with its nucleotide substrate (14). Alteration of other hinge residues of pol ␤ results in polymerases with strong mutator activity, both in vivo and in vitro (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Lysine 289 is located in ␣-helix N of the pol ␤ protein (14), which is important for accurate DNA synthesis (20)(21)(22)(23) because of its role in positioning the templating base during phosphodiester bond formation. We previously showed that the K289M protein (24) induces mutations within interrupted runs of like nucleotides in mouse cells at a 16-fold frequency over that of the WT enzyme.…”
mentioning
confidence: 99%
“…Pol ␤ lacks an intrinsic proofreading exonuclease and generates singlebase substitution errors at rates of 0.5-13 ϫ 10 Ϫ4 when filling short gaps (16,17). This fidelity is higher than predicted by free energy differences between correct and incorrect base pairing in solution (18), suggesting that like other DNA polymerases, pol ␤ contributes to the selectivity of nucleotide incorporation.Structural and biochemical evidence suggests that nucleotide selection by pol ␤ occurs at a step following initial, nonspecific dNTP binding (5,6,19,20). When DNA with a singlenucleotide gap is bound by pol ␤, a 90°kink is observed at the 5Ј-phosphodiester linkage of the template residue that base pairs with the incoming dNTP (5, 6).…”
mentioning
confidence: 99%
“…Structural and biochemical evidence suggests that nucleotide selection by pol ␤ occurs at a step following initial, nonspecific dNTP binding (5,6,19,20). When DNA with a singlenucleotide gap is bound by pol ␤, a 90°kink is observed at the 5Ј-phosphodiester linkage of the template residue that base pairs with the incoming dNTP (5, 6).…”
mentioning
confidence: 99%